Pengaruh Sistem Pengendalian Internal, Komite Audit, Dan Whistleblowing System Terhadap Pencegahan Fraud - Santi, Vidya Loka; Wafa, Zaenal (Value : Jurnal Manajemen dan Akuntansi, 2024)
The significant increase in fraud cases in Indonesia’s banking industry from 2016 to 2021, averaging over 300 cases per year, highlights the sector’s vulnerability to fraud. The financial industry, especially banking, accounts for 22.30% of total fraud cases, negatively impacting public trust and reputation. This study aims to examine the impact of internal control systems, audit committees, and whistleblowing systems in preventing fraud in banking companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. A quantitative approach is employed in this study, using secondary data from the annual reports of banking companies available on the IDX official website. The sample was selected using a purposive sampling technique, resulting in 42 banking companies that met the criteria. Data analysis was performed using panel data regression with the E-Views 12 software. The findings indicate that the internal control system and whistleblowing system have a significant effect on fraud prevention, whereas the audit committee does not have a significant impact. Collectively, however, these three variables contribute significantly to fraud prevention efforts.